2014
DOI: 10.1002/pbc.25300
|View full text |Cite
|
Sign up to set email alerts
|

Social competence in pediatric brain tumor survivors: Application of a model from social neuroscience and developmental psychology

Abstract: Pediatric brain tumor (BT) survivors are at risk for psychosocial late effects across many domains of functioning, including neurocognitive and social. The literature on the social competence of pediatric BT survivors is still developing and future research is needed that integrates developmental and cognitive neuroscience research methodologies to identify predictors of survivor social adjustment and interventions to ameliorate problems. This review discusses the current literature on survivor social function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 89 publications
(144 reference statements)
5
68
0
Order By: Relevance
“…Consistent with prior literature [15], caregivers highlighted the direct and indirect influences of insult-related factors on survivor SIP and social interactions. Caregivers discussed how insult-related factors affect survivors’ ability to engage in social activities, as well as how neurodevelopmental late effects impact survivor performance in social situations.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with prior literature [15], caregivers highlighted the direct and indirect influences of insult-related factors on survivor SIP and social interactions. Caregivers discussed how insult-related factors affect survivors’ ability to engage in social activities, as well as how neurodevelopmental late effects impact survivor performance in social situations.…”
Section: Discussionsupporting
confidence: 83%
“…Three themes were identified that are consistent with the social competence model and broader social ecological theory [15]. Themes include individual survivor factors and issues relevant to other systems affecting the survivor, including the family and broader social context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23, 26 AYA childhood brain tumor survivors can, therefore, experience profound social disconnections and suffer in social interactions with their peers. 27 AYA childhood brain tumor survivors also demonstrate more difficulty with social functioning as they age and most are more likely to become socially isolated.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…1 Unfortunately, children with brain tumors often report social strains associated with disruptions and daily hassles (i.e., activity limitations, fatigue, missing school, learning problems, teasing). 24 Teachers, parents, and peers describe brain tumor survivors as a group as having deficits in social competence and problems making friends compared with peers and normative data. 3,59 Evidence also suggests that survivors may underestimate peer relationship difficulties compared with healthy children.…”
Section: Introductionmentioning
confidence: 99%